Transjugular Intrahepatic Portosystemic Shunt: Indications, Contraindications, and Patient Work-Up - Copelan, Alexander; Kapoor, Baljendra; Sands, Mark (Seminars in Interventional Radiology, 2014)
The transjugular intrahepatic portosystemic shunt (TIPS) procedure is effective in achieving portal decompression and in managing some of the major complications of portal hypertension. While many clinicians are familiar with the two most common indications for TIPS placement, secondary prophylaxis of esophageal variceal hemorrhage and treatment of refractory ascites, evidence for its usefulness is growing in other entities, where it has been less extensively studied but demonstrates promising results. Newer indications include early utilization in the treatment of esophageal variceal hemorrhage, Budd–Chiari syndrome, ectopic varices, and portal vein thrombosis. The referring clinician and interventionist must remain cognizant of the contraindications to the procedure to avoid complications and potential harm to the patient. This review is designed to provide an in-depth analysis of the most common as well as less typical indications for TIPS placement, and to discuss the contraindications and appropriate patient evaluation for this procedure.
Keywords: transjugular intrahepatic portosystemic shunt; indications; contraindications; portal hypertension; interventional radiology